ANALISIS PENGARUH DANA ALOKASI KHUSUS (DAK) DAN DANA ALOKASI UMUM (DAU) TERHADAP BELANJA DAERAH KOTA PEKANBARU - Haloho Pebiantoni Jhon; Hamidi Wahyu; Jahrizal Jahrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research was conducted in Pekanbaru City. This study aims to see how the influence of the Special Allocation Fund (DAK) and the General Allocation Fund on Regional Expenditures in Pekanbaru City. This study uses secondary data from the Pekanbaru City Budget Report obtained from the Pekanbaru City Central Statistics Agency. The method used in this study is a data collection technique by directly taking data from the Pekanbaru City BPS. From the results of the research, the Special Allocation Fund has a positive but not significant effect on the regional expenditure of Pekanbaru City, which means that if there is an increase in the Special Allocation Fund, it will increase the regional expenditure of the city of Pekanbaru. The General Allocation Fund has a positive and significant effect on Pekanbaru City regional expenditure, which means that if there is an increase in the General Allocation Fund, it will increase Pekanbaru City regional expenditure. Keywords : Special Allocation Fund, General Allocation Fund, Regional Expenditure